Analyzing LDEX's Current Measurements in Lunar Orbit - Edwin Bernardoni; Mihály Horányi; Jamey R. Szalay (The Planetary Science Journal, 2023)
The Lunar Dust Experiment (LDEX) on board the Lunar Atmosphere and Dust Environment Explorer mission orbited the Moon from 2014 September to 2015 April and observed a dynamic, permanently present dust cloud produced by continual meteoroid bombardment. In addition to measuring individual ejecta with radii >0.3 μ m, LDEX also recorded an integrated current of the collective signal generated by the impacts of smaller ejecta particles. From this signal, we explore the potential for electrostatic dust lofting via twilight craters through correlation with changes in lunar topography. As the integrated current can contain numerous background contributions, we start by isolating regions of transient enhancements of this signal. A consistent lunar dayside enhancement is identified, with solar wind ions reflected as energetic neutral atoms shown to be a feasible source. We do not detect any enhanced integrated current correlated with the antihelion meteoroid bombardment or discernible enhancement due to electrostatic lofting via twilight craters, suggesting that electrostatic dust lofting does not contribute to the lunar dust environment at high altitudes (≫1 km).